The Effect of Using the Two Stay Two Stray Technique to Develop Young Learners’ Speaking Skills and Motivation - Annas Annas; Bustami Usman; Asnawi Muslem (English Education Journal, 2018)
This was a quantitative experimental study with the aim of finding out the result of using the Two-stay–two-stray (TS-TS) technique to develop young learners’ speaking skills, and motivation. The method used was a one group pre-test and post-test design: The instruments were the pre-test, the post-test and a questionnaire. The population was all the middle school students at SMPN2 in Idi Timur, East Aceh and the sample was the second grade students at SMPN2 Idi Timur chosen by using purposive sampling. The students’ achievements were tested by using a test and their motivation was measured by using a questionnaire. A pre-test and a post-test were given before and after the treatment. The results showed that the mean score from the pre-test was 54 and from the post-test it was 66. The result from the t-score was 9.37, while the critical value from the t-table was 2.06 at the level of significance of 0.01 it was 2.78 with 25 degrees of freedom. Since the result from the t-test was higher than the t-table, the alternative hypothesis was accepted. This proved that using the Two-stay-two-stray technique improved the speaking skills of the sample young learners. Regarding motivation, the students’ opinion about motivation in speaking English and the results from their pre-test were contradictory. Based on the answers to some questions in the questionnaire, the students showed lack of interest in developing their English speaking skills: Yet more than 50% of the students said that they practiced continuously so that their English speaking ability would get better. This means that these, students may still not be aware whether they are motivated or not in speaking English.